Dynamics of Visual Adaptation With Simultaneous Stimulation of Two Visual Pathways - Paz-Filgueira, Clemente; Tan, Michael; Elliott, Sarah; Cao, Dingcai (Frontiers in Neuroscience, 2021)
Primates’ retinal ganglion cells in different visual pathways have been shown to adapt independently (Current Biology 22 (2012) 220–224). However, the manner in which adaptation occurs under simultaneous stimulation of two visual pathways has not yet been explored. In this study, the dynamics of color afterimages were measured while stimulating one or two visual pathway using a time-varying afterimage paradigm. The dynamics of adaptation was approximately equivalent among the three primary visual pathways, but adaptation was slower for simultaneous stimulation of two visual pathways compared to the stimulation of one visual pathway. In addition, we found that the speed of adaptation also depends upon which two pathways are combined. We developed a two-stage adaptation model, both with the same dynamics, to account for the results with simultaneous stimulation of two pathways.